Investigation of modified ejector cycle on residential air conditioner with environmentally benign refrigerant of R290 - Sumeru, Kasni; Sukri, Mohamad Firdaus; Pratikto, Pratikto; Badarudin, Apip (Yildiz Technical University, 2020)
This paper investigates a modified ejector cycle (MEC) to further enhance the COP improvement of residential air conditioner (A/C), as compared to the standard ejector cycle (SEC). This paper also presents numerical and experimental studies of the MEC. Numerical approach of MEC performances was evaluated by using SEC cycle that had been developed by many researchers. In the experimental study of MEC, three motive nozzle diameters of 0.9, 1.0 and 1.1 mm were utilized. In addition, environmentally friendly refrigerant of R290 (propane) was used as a working fluid. The modeling results of residential A/C with the cooling capacity of 2.5 kW showed higher COP improvements of MEC than SEC for all entrainment ratios of the ejector. There was no COP improvement for SEC at a low entrainment ratio, whereas there are always COP improvements for all entrainment ratios for MEC. In addition, the experimental results showed the highest COP improvement of 16.67% was achieved with the motive nozzle diameter of 1.1 mm